Pemberdayaan Masyarakat Desa Melalui Ekonomi Kreatif: Strategi Pengembangan Ekonomi Pedesaan Di Desa Sukagalih, Kecamatan Sukaratu - Makarim, Siti Amirah; Dewi, Lati Sari (CV. SINAR HOWUHOWU, 2025)
This community service activity aims to enhance the capacity of the people of Sukagalih Village in developing local economic potential through a creative economy approach. The program involved seminars and training sessions focused on the utilization of local resources, development of creative products, and digital marketing strategies adapted to the village’s characteristics. The results of the activity showed an increase in community understanding of creative business opportunities based on local culture and surrounding natural resources. This initiative also encouraged the formation of community-based business groups as an initial step toward economic self-reliance in the village.